Strategi Pemasaran Melalui Program Afiliasi Digital - Hasirah; Lismaryanti; Yeni; Andi Irwin; Nur Azmi Azis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the marketing strategy through a digital affiliate program. This research approach collects data through a literature study, which involves reading literature from various sources including books, journals and reports using a qualitative and deductive approach. The findings in this study are that marketing strategies through digital affiliate programs have proven effective in increasing sales, expanding market reach, building trust and credibility, and marketing cost efficiency. In addition, by choosing the right affiliate, providing quality marketing materials, using effective affiliate platforms and networks, offering attractive incentives, and monitoring and analyzing performance regularly, companies can maximize the benefits of this digital affiliate program.